Research on the cultivation and construction of excellent academic atmosphere in colleges and universities - Dong Xiaohuan; Wu Yang; Huo Dingwen (ITM Web of Conferences, 2025)
Cultivating an excellent academic atmosphere in colleges and universities is crucial to the quality of professional teaching and talent cultivation. Establishing such an atmosphere is also vital to fulfilling the mission of nurturing talents for the Party and the country. Based on an analysis of the current status of academic atmosphere cultivation and construction in colleges and universities, this paper proposes innovative implementation plans for cultivating and building an excellent academic atmosphere from four aspects: leading the construction of academic atmosphere through party building and establishing a sound supervision and feedback system; promoting academic atmosphere construction through student organizations and innovating and improving the "three-full" education program (full-time, full-staff, and full-factor education); supporting academic atmosphere construction through services and enhancing the effect of collaborative education.